Leverage, Profitability, Environmental Performance, ISO 14001 Certification, and Public Ownership of Environmental Disclosure - Wati, Afifah Rachma; Kusumawati, Eny (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the influence of leverage, profitability, ISO 14001 certification, environmental performance, and public ownership on environmental disclosure among non-financial companies listed on the Indonesia Stock Exchange from 2021 to 2023. Using purposive sampling, 177 companies were selected, and the data were analyzed through multiple linear regression after passing classical assumption tests. The results show that environmental performance and public ownership significantly affect environmental disclosure, suggesting that firms with stronger environmental practices and wider public ownership are more inclined to disclose environmental information, possibly due to higher transparency demands and accountability pressures. However, leverage, profitability, and ISO 14001 certification do not significantly influence disclosure, indicating that internal financial metrics and formal certifications may not directly drive transparency in this context. This raises the need for further exploration of why these variables lack significance, potentially involving the nature of ISO implementation or varying stakeholder expectations. The study is limited by its focus on firm-level factors and does not incorporate external drivers such as regulatory requirements or industry pressures, which may also shape disclosure practices. Future research should integrate these broader contextual elements to gain a more comprehensive understanding of environmental disclosure determinants in emerging economies like Indonesia.